Total Mikroorganisme dan Respirasi Tanah pada Beberapa Tanah Sawah Anorganik di Denpasar - Soniari, Ni Nengah; Sutari, Ni Wayan Sri (Agrotrop : Journal on Agriculture Science; Vol 15 No 1 (2025), 2025)
Total Microorganism and Soil Respiration in Some Inorganic Rice Soils in Denpasar . Total microorganisms and soil respiration are indicators of soil fertility in terms of soil biological properties. The life of microorganisms in the soil determines the smoothness of the processes that occur in the soil which are closely related to the provision of nutrients to support plant growth. Soil pollution due to fertilizer and pesticide residues can disrupt the comfortable life of soil microorganisms. This research aims to determine the total number and activity of microorganisms in intensively planted rice fields in the city of Denpasar. The urgency of this research is to obtain data that describes the biological conditions of inorganic rice fields in the city of Denpasar. This research was carried out by taking composite samples of inorganic rice field soil in several locations in the city of Denpasar. The parameters observed were the total number of soil microorganisms, soil respiration, organic C, total N, pH and soil salt content. Soil analysis was carried out at the Soil and Environmental Science Laboratory, Faculty of Agriculture, Udayana University. Obtaining data on the biological conditions of inorganic rice fields in Denpasar is important for recommendations for improving sustainable management of rice fields. The research results showed that the inorganic rice fields from 10 subaks surveyed in Denpasar had air-dry soil water content that was all low, C-organic varied from low to high and N-total was very low to low. The highest total of paddy soil microorganisms was found in the Tegal lantang subak (125x10 5 cfu/g) and the lowest in the Sembung subak (64 x 10 5 cfu/g). The highest soil respiration occurred in the Pakel subak (8.74 mg C-CO 2 /kg/day) and the lowest in the Renon subak (5.66 mg C-CO 2 /kg/day). Soil biological properties such as total microorganisms and soil respiration depend on environmental conditions and the management of rice fields by farmers.